2013
DOI: 10.3899/jrheum.121302
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lipid-lowering Agents in Rheumatoid Arthritis: A Population-based Cohort Study

Abstract: Objective Rheumatoid arthritis (RA) is associated with an increased risk of cardiovascular disease and mortality. Lipid-lowering therapy is reportedly underused in patients with RA. However, longitudinal cohort studies comparing the use of lipid-lowering medications in patients with RA vs the general population are lacking. Methods Cardiovascular risk factors, lipid measures and use of lipid-lowering agents were assessed in a population-based inception cohort of patients with RA and a cohort of non-RA subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Although cardiovascular disease contributes to half of the mortality occurring during RA [1], lipid-lowering agents are underused in RA despite management guidelines to reduce LDLc levels as recommended by ATP III [28,29]. In the present RA cohort, only 17.7% of patients aged 40 to 65 and 25.8% of patients over the age of 65 received a statin, while [31].…”
Section: Discussionmentioning
confidence: 97%
“…Although cardiovascular disease contributes to half of the mortality occurring during RA [1], lipid-lowering agents are underused in RA despite management guidelines to reduce LDLc levels as recommended by ATP III [28,29]. In the present RA cohort, only 17.7% of patients aged 40 to 65 and 25.8% of patients over the age of 65 received a statin, while [31].…”
Section: Discussionmentioning
confidence: 97%
“…This is concerning as patients with RA are at increased risk for cardiovascular events and are often at sufficiently high risk to require statin therapy [13] [22]. A previous study from this same population found that patients with RA were not adequately initiated on lipid lowering therapy when they met clinical guidelines set by the National Cholesterol Education Program (NCEP) and their lipids were tested less frequently than individuals from the general population [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Assessment of adherence to cardiovascular disease quality indicators at two Canadian university clinics showed low performance rates for several measures 154. Moreover, rheumatoid arthritis patients are less likely than other patients to have lipid measurements obtained,155156 with less than 50% of eligible rheumatoid arthritis patients in the 5% random sample of Medicare receiving appropriate lipid screening 157. Use of lipid lowering treatment for rheumatoid arthritis patients fulfilling the National Cholesterol Education Program’s Adult Treatment Panel III criteria was suboptimal, with only 27% starting therapy 155.…”
Section: Management and Prevention Of Cardiovascular Disease In Rheummentioning
confidence: 99%
“…Moreover, rheumatoid arthritis patients are less likely than other patients to have lipid measurements obtained,155156 with less than 50% of eligible rheumatoid arthritis patients in the 5% random sample of Medicare receiving appropriate lipid screening 157. Use of lipid lowering treatment for rheumatoid arthritis patients fulfilling the National Cholesterol Education Program’s Adult Treatment Panel III criteria was suboptimal, with only 27% starting therapy 155. In a separate cross sectional study, 38% of rheumatoid arthritis patients without previous cardiovascular disease were deemed at risk, and yet only 7% were receiving statins 158.…”
Section: Management and Prevention Of Cardiovascular Disease In Rheummentioning
confidence: 99%